EUSTRESS, LEARNING ENGAGEMENT, AND WORKABLE STRATEGIES OF DCBLT IN ENGLISH FOR ENGINEERING - Aini, Jihan Nawal; Anwar, Khoirul; Arifani, Yudhi (University of Kuningan, 2023)
Attention to eustress related to learning engagement among ESP learners utilizing Digital Content-Based Language Teaching (DCBLT) remains notably insufficient. This research aims to identify the levels and relationships between eustress and learning engagement, as well as the identification of workable teaching strategies when implementing DCBLT. Employing a mixed-method approach, this study utilizes quantitative data (questionnaire responses) from 43 students and qualitative data (in-depth interviews) from three English for Engineering language instructors. The analysis procedure for quantitative data employed the Spearman rank correlation test, while qualitative data was analyzed using thematic analysis. The results indicate that the levels of eustress and learning engagement among students are highly satisfactory. Moreover, eustress correlates positively and strongly with increased learning engagement. The data also reveals the existence of several workable DCBLT teaching strategies, encompassing the pre-teaching phase (stimulating idea generation, fostering brainstorming, establishing connections, and motivating learners), the whilst-teaching phase (employing a student-centered learning approach, including individual tasks, group work, and quizzes via the DCB platform), and the post-teaching phase (assessing, verifying, and reviewing learners' comprehension). Research recommendations are also presented in the concluding section to fortify and extend the findings of this study.